Panggilan (Calling) dan Kesejahteraan di Tempat Kerja pada Karyawan Kehutanan - Firmansyah, Kresna Reihan; Riasnugrahani, Missiliana (Universitas Islam Indonesia, 2022)
Working conditions with a high risk of safety and health can reduce employees’ well- being in the workplace. Well-being in the workplace is essential in supporting employee performance that prevents employees from error and negligent behavior. Therefore, this study aims to determine the relationship between calling and well-being for forestry employees. Our hypothesis is search for calling dimension has a negative correlation with employees’ well-being at work, and the presence of calling has a positive correlation with employees’ well-being at work. Through the purposive sampling technique, 130 employees are willing to participate in this study. Data collection uses the Calling and Vocation Questionnaire (CVQ) and the Eudaimonic Well-being at Work Scale (EWWS), with high-reliability scores. The results of data analysis showed that both the dimensions of calling–search and the presence–had a significant positive relationship with well-being at work. Employees who seek a calling, and those who perceive a calling, feel a sense of well-being at work.